Central nystagmus plus ABCD2 identifying stroke in acute dizziness presentations. (9th June 2021) - Wang, Weiheng; Zhang, Yixin; Pan, Qi; Liu, Juan; Zhu, Yinglin; Tan, Ge; Zhan, Qunling; Zhou, Jiying
Abstract: Objective: The objective was to explore the ability of head impulse‐nystagmus‐test of skew (HINTS) combined with ABCD 2  score to identify cerebrovascular causes of dizziness. Materials and Methods: We prospectively recruited 85 patients with acute onset of dizziness from September 2016 to December 2018 and analyzed their clinical characteristics, ABCD 2  scores, HINTS, and neuroimages data. Results: Acute stroke was identified by MRI in 21 of 85 patients. The mean ± SD ABCD 2  scores were significantly higher among patients with acute stroke than those without acute stroke (4.0 ± 0.8 h vs. 2.5 ± 0.7 h, p  < 0.01). The majority (71.4%) of patients with cerebrovascular causes had central pattern of nystagmus at the initial 48 h from symptoms onset. The sensitivity and specificity of HINTS were 100% and 87% for the presence of stroke in patients with nystagmus. When combined central pattern of nystagmus and ABCD 2  ≥ 4, the sensitivity increased to 100% for identifying cerebrovascular causes. Nystagmus were absence at time of examination in 16.5% of our patients, and ABCD 2  scores in patients who had cerebrovascular diagnoses were all ≥ 4. Conclusion: HINTS examinations could efficiently differentiate stroke from nonstroke under the condition that patients remaining symptomatic, including spontaneous or gaze‐evoked nystagmus. It is more practical to apply the combination of central pattern of nystagmus and ABCD 2  ≥ 4 in ED setting. If patients were absence of central nystagmus at admission, cerebrovascular event should be a priority diagnosis when their ABCD 2  ≥ 4.